2016
DOI: 10.1002/er.3484
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid storage designs for continuous operation of solar-powered LiBr-water absorption air-conditioning

Abstract: SUMMARYThe design of the energy storage serving solar-powered LiBr-water absorption air-conditioning systems to meet 24-h a day operation is an important parameter that determines the performance of the system and optimizes its components. Introducing hybrid storage designs can improve system performance, reduce collector size, lower storage tank capacity, and hence make 24-h a day operating solar-powered LiBr-water absorption air-conditioning systems more feasible. Moreover, hybrid storage designs will ensure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In Equation (5), e is the availability per unit mass (kJ kg −1 ), _ E represents the availability flow rate (kW), _ m is the mass flow rate (kg s −1 ), and h 0 , s 0 , and T 0 are the enthalpy per unit mass (kJ kg −1 ), the entropy per unit mass (kJ kg −1 K −1 ), and the temperature (K) of the reference state, respectively. The value of rate of the availability destruction _ E D À Á can be obtained from the availability balance.…”
Section: Availability Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Equation (5), e is the availability per unit mass (kJ kg −1 ), _ E represents the availability flow rate (kW), _ m is the mass flow rate (kg s −1 ), and h 0 , s 0 , and T 0 are the enthalpy per unit mass (kJ kg −1 ), the entropy per unit mass (kJ kg −1 K −1 ), and the temperature (K) of the reference state, respectively. The value of rate of the availability destruction _ E D À Á can be obtained from the availability balance.…”
Section: Availability Determinationmentioning
confidence: 99%
“…Therefore, there is an unprecedented need for an environment friendly energy saving cooling system. As a feasible option, vapor absorption cooling systems (VACSs) have received significant attention for harnessing waste and renewable energy sources, like vehicle waste heat, 3 solar energy, 4,5 geothermal energy, 6 and so on. VACS finds widely in industries, malls, and theatres where the above heat sources can be utilized to superheat the refrigerant.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Jani et al performed a simulation study on the solid desiccant assisted VC air‐conditioning system for a small test chamber under hot and humid environment to show the effect of ambient humidity and temperature on the proposed system's coefficient of performance ( COP ). Shaarawi and Ugla proposed the concept of hybrid cold and refrigerant energy storage device for continuous working of LiBr‐water based absorption air cooling system. They optimized the sizes of different components of the air‐conditioning system.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the cooling system continued to operate for a while after sunset and has an enhanced COP. El‐Shaarawi and Al‐Ugla studied to investigate four different configurations of hybrid storage for a 24‐hour operation of solar‐powered LiBr‐water absorption AC using ambient conditions of a family house in Dhahran City, Saudi Arabia that has a total daily cooling load of 120 kWh. They already stated that hybrid storage design for absorption chiller increases the performance and reduces the collector size.…”
Section: Introductionmentioning
confidence: 99%